METHODS OF DEVELOPING IDEOLOGICAL IMMUNITY AMONG YOUTH BASED ON THE SCIENTIFIC HERITAGE OF THE TERMIZIY SCHOLARS - Azim Kakhharovich Madjidov (Modern American Journals, 2026)
This article examines the influence of the scientific heritage of the Termiziy scholars on the development of ideological immunity among youth. Practical recommendations are also provided, and their essence is analyzed.
Keywords: Moral and spiritual education, educational program, social event, narrative, ideological immunity, spiritual maturity, national values, mentor, honesty, ethical standards, “Termiziy Week”, brainwashing, life stance, neighborhood, and family.